EXPLORING STUDENTS PERCEPTION AND BELIEF TOWARD THE INTERNET USAGE IN ENGLISH LEARNING - Dodi Erwin Prasetyo (Balai Besar Guru Penggerak Jawa Timur, 2022)
Since the spread of Covid 19 pandemic around the world, the utilization of internet as online media is a must. The use of internet in the education field stresses on students to hugely adapt their learning process. Therefore, this study aimed at finding to explore of students’ perception and belief toward the internet usage in terms of what their perception and belief toward the internet usage, how correlation between their perception and belief toward the internet usage and what differences between male and female students on the perception and belief toward the internet usage. This study recruited 25 junior high school students. The data was gathered via questionnaire. The findings highlighted three points. The first point was that students gained positive perception and belief toward the internet usage in learning. The second point was that the existence of correlations between the perception and belief (significance two tailed at .044). However, the correlation was at the moderate level (r-value at .551). The third point was that there were no differences between male and female students in their perception (significance two tailed at .623) and belief (significance two tailed at .891) toward the internet usage. The suggestions are offered pedagogics and future researches AbstrakSejak merebaknya pandemi Covid 19 di seluruh dunia, penggunaan internet sebagai media daring adalah suatu keharusan. Penggunaan internet di dunia pendidikan menekankan kepada para siswa secara massif untuk beradaptasi selama proses pembelajaran. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi persepsi para siswa dan juga keyakinan mereka terhadap penggunaan internet dalam hal bagaiamana persepsi para siswa dan keyakinan mereka terhadap penggunaan internet untuk media pembelajaran, bagaiamana korelasi antara persepsi dan keyakinan mereka terhadap penggunaan internet, dan apa perbedaan antara persepsi dan keyakinan siswa laki – laki dan perempuan terhadap penggunaan internet. Penelitian ini merekrut 25 siswa sekolah menengah pertama. Data dikumpulkan melalui angket. Hasil penelitian ini teridir dari tiga poin. Poin pertama bahwa para siswa mempunyai perspei dan keyakinan yang baik terhadap penggunaan internet untuk media pembelajran mereka. Poin kedua bahwa adanya korelasi antara persepsi dengan keyakinan terkait penggunaan internet untuk media pembelajaran (nilai signifikan pada 0.044). Tetapi, korelasi tersebut ada pada level menengah (nilai R pada 0.551). poin ketiga bahwa tidak ada perbedaan antara para sisqa laki laki dan perempuan terkait persepsi (nilai signifikan 0.623) dan keyakinan (nilai signifikan 0.891) mereka di dalam penggunaan internet. Saran – saran diberikan dalam kontek pedagogik and penelitain kedepannya.